2021
DOI: 10.1038/s41598-021-89394-y
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and structural insights into Rab12 interactions with RILP and its family members

Abstract: Alongside its biosynthetic functions, the small GTPase Rab12 negatively regulates mast cell (MC) exocytosis by its interaction with RILP to promote retrograde transport of the MC secretory granules. Given the role of Rab effectors in mediating Rab functions, in this study we used biochemical and in silico tools to decipher Rab12 interactions with its RILP family effectors. We show that Rab12 interacts with RILP, RILP-L1 and RILP-L2 independently of each other, whereby lysine-71, in mouse Rab12, is critical for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Rab12 localizes to the EEs and ERC and controls the transport of specific cargo, such as TfR, from the ERC to lysosomes [ 125 ] and stimulates autophagy [ 131 ], autophagosome trafficking [ 132 ], and retrograde transport from the ERC to TGN [ 133 ]. It has been suggested that Rab12 facilitates the direct or indirect fusion of RE/ERC-derived compartments with lysosomes [ 125 ] and links autophagosomes to motor proteins to facilitate autophagosome trafficking [ 132 ].…”
Section: Host Cell Signatures Within Virionsmentioning
confidence: 99%
“…Rab12 localizes to the EEs and ERC and controls the transport of specific cargo, such as TfR, from the ERC to lysosomes [ 125 ] and stimulates autophagy [ 131 ], autophagosome trafficking [ 132 ], and retrograde transport from the ERC to TGN [ 133 ]. It has been suggested that Rab12 facilitates the direct or indirect fusion of RE/ERC-derived compartments with lysosomes [ 125 ] and links autophagosomes to motor proteins to facilitate autophagosome trafficking [ 132 ].…”
Section: Host Cell Signatures Within Virionsmentioning
confidence: 99%